Pengaruh Pembiayaan Mudharabah, Musyarakah, Murabahah, Ijarah Dan Qardh Terhadap Tingkat Profitabilitas Bank Syariah Indonesia - Ariyanti, Okta Nuria; Sawitri, Riska Agi (Universitas Islam Negeri Raden Intan Lampung, 2023)
Profitability is used to measure effectiveness in utilizing owned assets. The greater the profitability, the better the company's performance, because the rate of return is greater. This study aims to examine and analyze the effect of mudharabah, musyarakah, murabahah, ijarah and qardh financing on the profitability of Indonesian Islamic Banks. The research method used is a quantitative type. The data used is secondary data in the form of financial reports and the sample in this study is quarterly financial reports for the 2021-2022 period obtained through the official website of Bank Syariah Indonesia. The data analysis technique used is multiple linear regression analysis. The results of this study are that mudharabah financing has a significant effect on profitability, musyarakah has no effect, murabahah has no effect, ijarah has no effect and qardh has no effect. Simultaneously it is concluded that the independent variables simultaneously have a significant effect on the dependent variable at Bank Syariah Indonesia. The results of the analysis of the coefficient of determination is 0.887. This means that the ability of the independent variable to explain the dependent variable is 88.7%, the remaining 11.3%.